2023
DOI: 10.3748/wjg.v29.i38.5374
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional study of cholecystokinin-A receptors on the interstitial Cajal-like cells of the guinea pig common bile duct

Dan Xu,
Song-Lin Ma,
Man-Lin Huang
et al.

Abstract: Intraductal papillary neoplasms of the bile duct (IPNBs) represent a rare variant of biliary tumors characterized by a papillary growth within the bile duct lumen. Since their first description in 2001, several classifications have been proposed, mainly based on histopathological, radiological and clinical features, although no specific guidelines addressing their management have been developed. Bile duct neoplasms generally develop through a multistep process, involving different precursor pathways, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been found that the higher the degree of cholesterol saturation in bile, the lower the density of ICLCs, which also suggests that the probability of gallbladder dysmotility is relatively higher in populations in which bile exhibits a tendency to lithogenicity ( Pasternak et al, 2013 ). Among the many gastrointestinal hormones Cholecystokinin (CCK) has a role in stimulating gallbladder contraction, and CCK can modulate Common Bile Duct (CBD) contraction by stimulating CCK-A receptors on ICLCs( Xu et al, 2023 ). Telocytes (TCs), a new type of interstitial cells, have recently been identified in many organs, including gallbladder.…”
Section: Traditional Chinese Medicine To Prevent Recurrence Of Cbdsmentioning
confidence: 99%
“…It has been found that the higher the degree of cholesterol saturation in bile, the lower the density of ICLCs, which also suggests that the probability of gallbladder dysmotility is relatively higher in populations in which bile exhibits a tendency to lithogenicity ( Pasternak et al, 2013 ). Among the many gastrointestinal hormones Cholecystokinin (CCK) has a role in stimulating gallbladder contraction, and CCK can modulate Common Bile Duct (CBD) contraction by stimulating CCK-A receptors on ICLCs( Xu et al, 2023 ). Telocytes (TCs), a new type of interstitial cells, have recently been identified in many organs, including gallbladder.…”
Section: Traditional Chinese Medicine To Prevent Recurrence Of Cbdsmentioning
confidence: 99%